Study of Physical and Chemical and Biochemical Indicators Lamb - Abzhanova Sholpan; Baibolova Lyazzat; Dikhanbaeva Fatima; Kizatova Maygul; Mukhtarkhanova Rauan (Journal of Pharmacy and Nutrition Sciences, 2019)
The main sources of animal protein are meat, milk, eggs and fish. Meat and meat products contain half of the protein a person needs, as well as all the fats, carbohydrates, hormones and other biologically active substances necessary for his life. Meat is the optimal supplier of trace elements such as iron, zinc and selenium. The aim of the work is the need to conduct research on the development of promising methods for processing raw meat and expanding the range, preparing it for the manufacture of high-quality meat products. The presented article is aimed at the development of scientifically-based solutions necessary for the implementation of the technology for the production of combined products through a combination of meat and vegetable raw materials.